2017
DOI: 10.1175/bams-d-16-0297.1
|View full text |Cite
|
Sign up to set email alerts
|

Urban Finescale Forecasting Reveals Weather Conditions with Unprecedented Detail

Abstract: Urban landscapes impact the lives of urban dwellers by influencing local weather conditions. However, weather forecasting down to the street and neighborhood scale has been beyond the capabilities of numerical weather prediction (NWP) despite the fact that observational systems are now able to monitor urban climate at these scales. In this study, weather forecasts at intra-urban scales were achieved by exploiting recent advances in topographic element mapping and aerial photography as well as looking at detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 39 publications
0
86
0
2
Order By: Relevance
“…Recent studies by Wolf-Grosse et al [28] and Ronda et al [18], however, showed the importance of topographic effects and consideration of water bodies at city scale. Therefore, these effects will be considered in a follow-up study, focusing on their combined influence on ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Wolf-Grosse et al [28] and Ronda et al [18], however, showed the importance of topographic effects and consideration of water bodies at city scale. Therefore, these effects will be considered in a follow-up study, focusing on their combined influence on ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no distinction was made for different land use or land covers like water bodies or roads (i.e., no difference in surface heat flux). This simplification prevented the development of secondary circulations like sea-breeze, which would otherwise affect city ventilation [18].…”
Section: Simulation Setupmentioning
confidence: 99%
“…Holt and Pullen, 2007;Miao et al, 2009;Bohnenstengel et al, 2011;Chen et al, 2011) although smaller cities and neighbourhood-scale features within larger ones cannot. With the continuing advances in available computer power a number of operational centres are now carrying out research into a new generation of city-scale models at turbulence-permitting (O(100 m)) scales (Leroyer et al, 2014;Ronda et al, 2017). The motivation for this is to improve small-scale forecasts of hazards (urban heat, flooding, poor air quality) on both weather and climate time-scales.…”
mentioning
confidence: 99%
“…Similar UM configurations were also used to investigate the resolution dependence of the representation of deep convection over the United Kingdom as part of the DYnamical and Microphysical Evolution of Convective Storms project (DYMECS: Hanley et al, 2015;Stein et al, 2015). Elsewhere in the community there have been a number of experiments with sub-km NWP models of cities (Leroyer et al, 2014;Ronda et al, 2017).…”
mentioning
confidence: 99%
“…Interactions with the overlying atmosphere in an NWP model can be coupled to a surface model either in a full 3D set-up or in a 1D set-up (single-column model; SCM). Many studies have investigated the effects of surface parametrization on boundary-layer representation (e.g., Pigeon et al, 2007;Flagg and Taylor, 2011;Ferrero et al, 2018), surface energy balance (e.g., Pigeon et al, 2007;Loridan et al, 2013;Demuzere et al, 2017), urban heat islands (e.g., Miao et al, 2009;Bohnenstengel et al, 2011;Nemunaitis-Berry et al, 2017;Ronda et al, 2017) and other mesoscale phenomena (e.g., Chen et al, 2011b). The majority of the studies use a 3D set-up, which limits the ability to link the model response to changes in surface parameters and investigate feedback mechanisms in detail.…”
Section: Introductionmentioning
confidence: 99%